An asymmetric Doherty amplifier with class‐J mode in GaAs HBT technology for n78 frequency band. Issue 10 (27th July 2022) - Zhou, Jiuding; Yi, Chupeng; Wang, Yuchen; Liu, Wenliang; Lu, Yang; Hou, Bin; Ma, Xiaohua; Zhao, Yuanfu; Hao, Yue
Abstract: This paper presents a compact GaAs HBT Doherty power amplifier (DPA) with integrated three stages for the 5G application. Different from most GaAs HBT PAs, this PA is designed in the asymmetric Doherty structure with a class‐J operation mode. The output parasitic capacitance of the carrier amplifier is extracted and absorbed into the matching network, generating a π‐type structure and realizing the impedance inverter. In addition, the phase alignment between the carrier and peaking amplifier is implemented skillfully by employing input, inter‐stage, and output matching networks. The fabricated Doherty PA achieved a high gain of 32.5–34.1 dB and P1dB of 34–34.5 dBm. The 42.8%–45.1% and 28.7%–30.1% PAE are obtained at P1dB and 7.5 dB PBO under a continuous‐wave signal test across 3.3–3.6 GHz, respectively. A 100 MHz 64‐quadratic‐amplitude modulated (QAM) signal with a 7 dB peak‐to‐average power ratio (PAPR) is also applied to the proposed DPA at 3.5 GHz. The measured adjacent channel power ratio (ACPR) is lower than −37.7 dBc without any linearization.